Limitasi ‘Iddah dan Ihdad Wanita Pekerja di Desa Jogoroto Kecamatan Jogoroto Kabupaten Jombang Perspektif Maslahah Mursalah - Mubarok, Muham Muhammad; Hasbillah, Ahmad Ubaidi (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
As the era progresses, the emancipation voiced by women has become a reality. Nowadays it has changed 180 degrees. It is not uncommon for government seats or posts that were previously thought to only be occupied by men to be occupied by women, including those who are currently undergoing the 'iddah period. This has become an urgent problem for society that must be resolved by fiqh, one of the the only community in Jogoroto Village, the majority of whose wives also work to support their families, so the researchers felt this was very important to discuss. The objectives of this research are: First, to summarize the practices of 'iddah and ihdad of working women in Jogoroto Village. Second, Knowing the limitations of 'iddah and ihdad for working women from the perspective of maslahah murlah. To obtain relevant results, researchers use mixed methods, by combining progressive law with analyzing values ​​and laws that apply in the field (field research) as well as analyzing literature studies as arguments to strengthen the research, so that readers can understand the process and reasons Fiqh answers these problems. In practical terms, women workers in Jogoroto Village carry out 'iddah in accordance with the Shari'a, but in practical ihdad there are several actions that are in accordance with the concept of maslahah murlahah. they do not stifle their productivity by blindly staying at home, but other ihdad practices are considered too lenient in terms of leaving the house.